From Crisis to Recovery: Understanding the Impact of COVID-19 on Indonesian Employment Dynamics - Sugiharti, Lilik; Esquivias, Miguel Angel; Aditina, Neny; Sukma, Weni Lidya (Journal of Population and Social Studies [JPSS], 2025)
This research analyzes the impact of the economic disruption caused by the COVID-19 pandemic on Indonesia’s labor market by utilizing data from SAKERNAS, or the National Labor Force Survey, for 2020 and 2021. A logistic regression model is used to analyze the impact of sociodemographic factors, job-related variables, and the Kartu Prakerja (a pre-employment program focused on training and skill development) on unemployment, labor force participation, and reduced working hours caused by the economic disruption of COVID-19. The findings underscore the enduring repercussions of the pandemic on employment landscapes, with pronounced impacts observed among older workers, married individuals, less educated workers, and urban residents. The manufacturing and service sectors experienced more significant implications than agriculture, revealing sector-specific challenges. Kartu Prakerja influenced working hour reductions in 2021, showing the effects of evolving government intervention. Increased Internet use was linked to reduced working hours, signaling the need for accelerated digital skill programs for jobs dependent on Internet use.